Antioxidant Effects of Aqueous Leaves Extracts of Launaea Taraxacifolia in Benzene-Induced Haematotoxicity in Albino WistarRats - Progress Arhenrhen OBAZELU* and Abieyuwa Peace OMOREGIE (Sokoto Journal of Medical Laboratory Science)
Launaea taraxacifolia, a plant renowned in diverse traditional medicines for its health- enhancing qualities, has garnered interest owing to its documented antioxidant attributes. Given the potential anti-oxidative and cytoprotective properties of Launaea taraxacifolia extracts, there is a growing interest in investigating their effects on cellular pathways such as nuclear factor erythroid 2-related factor 2 (NRF-2) and heme oxygenase | (HO-1) in the context of benzene- induced haematotoxicity. Understanding the interactions between these extracts and the cellular defense mechanisms could provide valuable insights into their potential as therapeutic agents. The aim of this study was to determine the antioxidant effects of aqueous leaf extracts of Launaea taraxacifolia in benzene induced haematotoxicity in albino Wistar rats. A total of sixty (60) adult male albino Wistar rats were divided into six groups namely groups A, B, C, D, E and F, representing control, benzene group, cyclophosphamide group, benzene + 100mg/kg Launaea taraxacifolia, benzene + 200mg/kg Launaea taraxacifolia and benzene + 400mg/kg Launaea taraxacifolia respectively. mRNA expression of NRF-2 and HO-1 were determined using polymerase chain reaction. Data obtained was analyzed by the Statistical Package for Social Science (SPSS) software. Comparison amongst the study groups showed that mRNA expression of NRF-2 was significantly higher in group E when compared to group B (p<0.05).The mRNA expression of NRF-2 was significantly lower in group F than group A (p<0.05). The mRNA expression of HO-1 in group B, C, D, E and F was significantly lower than group A (p<0.05). The mRNA expression of HO-1 in group C, D and F was significantly lower than group B (p<0.05). This study concludes that benzene induced a reduction in NRF-2 and HO-1 mRNA expression. Launaea taraxacifolia reversed the observed effects of benzene on NRF-2 but not on HO-1